Odpowiedź:
Szczegółowe wyjaśnienie:
4.
a) 5 * (9 * 10^7) = 45 * 10^7 = 4,5 * 10^8
b) 4 * 10³ * 7 = 28 * 10³ = 2,8 * 10^4
c) 8 * (3 * 10^(-7)) = 24 * 10^(-7) = 2,4 * 10^(-6)
d) (8 * 10^6) * (4 * 10^9) = 32 * 10^15 = 3,2 *10^16
e) (7 * 10^(-3)) * (2 * 10^7) = 14 * 10^4 = 1,4 * 10^5
f) (16 * 10²) : (8 * 10^(-5)) = [16 * 10²]/[8 * 10^(-5)] = 2 * 10² * 10^5 = 2 * 10^7
g) 5,4 * 10^8 + 3 * 10^11 = 5,4 * 10^8 + 3000 * 10^8 = 3005,4 * 10^8 =
= 3,0054 * 10^11
h) 1,8 * 10^12 - 20 * 10^9 = 1800 * 10^9 - 20 * 10^9 = (1800-20) * 10^9 =
= 1780 * 10^9 = 1,78 * 10^12